Heal the Healers: A pilot study evaluating the feasibility, acceptability, and exploratory efficacy of a Transcendental Meditation intervention for emergency clinicians during the coronavirus disease 2019 pandemic. Issue 6 (29th December 2021) - Azizoddin, Desiree R.; Kvaternik, Noelia; Beck, Meghan; Zhou, Guohai; Hasdianda, Mohammad Adrian; Jones, Natasha; Johnsky, Lily; Im, Dana; Chai, Peter R.; Boyer, Edward W.
Abstract: Objective: Emergency clinicians face elevated rates of burnout that result in poor outcomes for clinicians, patients, and health systems. The objective of this single‐arm pilot study was to evaluate the feasibility of a Transcendental Meditation (TM) intervention for emergency clinicians during the coronavirus disease 2019 (COVID‐19) pandemic and to explore the potential effectiveness in improving burnout, sleep, and psychological health. Methods: Emergency clinicians (physicians, nurses, and physician‐assistants) from 2 urban hospitals were recruited to participate in TM instruction (8 individual or group in‐person and remote sessions) for 3 months. Session attendance was the primary feasibility outcome (prespecified as attending 6/8 sessions), and burnout was the primary clinical outcome. Participant‐reported measures of feasibility and validated measures of burnout, depression, anxiety, sleep disturbance, and stress were collected at baseline and the 1‐month and 3‐month follow‐ups. Descriptive statistics and linear mixed‐effects models were used. Results: Of the 14 physicians (46%), 7 nurses (22%), and 10 physician‐assistants (32%) who participated, 61% were female ( n = 19/32). TM training and at‐home meditation practice was feasible for clinicians as 90.6% ( n = 29/32) attended 6/8 training sessions and 80.6% self‐reported meditating at least once a day on average. Participants demonstrated significant reductions in burnout ( P < .05; effect sizes, Cohen's d = 0.43–0.45) and in symptoms of depression, anxiety, stress, and sleep disturbance ( P values < .001; Cohen's d = 0.70–0.87). Conclusion: TM training was feasible for emergency clinicians during the COVID‐19 pandemic and led to significant reductions in burnout and psychological symptoms. TM is a safe and effective meditation tool to improve clinicians' well‐being.